Effects of glucagon‐like peptide‐1 receptor agonists on cardiovascular and renal outcomes: A meta‐analysis and meta‐regression analysis. Issue 6 (21st February 2022) - Yoshiji, Satoshi; Minamino, Hiroto; Tanaka, Daisuke; Yamane, Shunsuke; Harada, Norio; Inagaki, Nobuya
Abstract: Aim: To evaluate the cardiovascular and renal outcomes of glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) and the associations between these outcomes and HbA1c or weight reduction. Materials and Methods: We searched PubMed/MEDLINE, EMBASE, and CENTRAL databases for randomized, placebo‐controlled trials of GLP‐1 RAs reporting major adverse cardiovascular events (MACE; a composite of cardiovascular mortality, stroke, and myocardial infarction) as the primary outcome. We conducted a meta‐regression analysis of primary and secondary outcomes with HbA1c or weight reduction following a meta‐analysis with a random‐effects model for these outcomes. Results: We extracted data of 60 800 individuals from eight eligible studies (ELIXA, LEADER, SUSTAIN‐6, EXSCEL, HARMONY, PIONEER 6, REWIND, and AMPLITUDE‐O). GLP‐1 RAs reduced MACE (hazard ratio [HR] 0.86; 95% CI: 0.80‐0.93; P  < .001) and secondary outcomes including the composite renal outcome (0.80; 0.73‐0.87; P  < .001). In meta‐regression analysis, every 1% reduction in HbA1c was associated with 26% and 35% decreases in the logarithm of HR of MACE ( P  = .044; R 2  = 0.65) and the composite renal outcome ( P  = .040; R 2  = 0.85), respectively. On the contrary, weight reduction was not associated with any outcome, including MACE ( P  = .390). Conclusions: The reduction in HbA1c, but not body weight, is associated with cardiovascular and renal outcomes. The magnitude of HbA1c reduction can be a surrogate for the cardiovascular and renal benefits of treatment with GLP‐1 RAs.